REPLACEMENT EFFECT OF COMMERCIAL RATIONS WITH FLOUR OF FERMENTED MUNG BEAN SPROUTS PEEL ON THE COMMERCIAL PIECES OF BALI DUCK CARCASS - I K. A., Purnawan; Puger, A. W.; Puspani, E. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
Mung bean sprouts peel is part of the mung bean sprouts that are not utilized and wasted. This study aims to determine the effect of replacing commercial rations with fermented mung bean sprouts peel flour on commercial pieces of male bali duck carcass. This study uses a completely randomized design (CRD) with three treatments and five replications. The treatment given is; P0 (CP 511 commercial ration of 100%), P1 (12.5% ??replacement of commercial rations with fermented mung bean sprouts peel flour) and P2 (substitute 25% of commercial rations with fermented mung bean sprouts peel flour). The variables observed in this study were the percentage of chest, percentage of upper thigh, percentage of lower thigh, percentage of wing, percentage of back. The results showed that replacing up to 25% of the commercial ration with flour of  fermented mung bean sprout peel  (P2) decreased chest percentage by 12.27% (P <0.05 raising upper thigh percentage by 13,92% (P <0.05 ) and lower thighs 12.08% (P <0.05) and had no significant effect (P> 0.05) on wing percentage and back percentage compared to P0. Based on the results of the study, it can be concluded that the replacement of commercial rations with flour of fermented mung bean sprouts peel by up to 25% decreases the percentage of the chest, increases the percentage of lower thighs and upper thighs but has no effect on the percentage of wings and backs Keywords : Mung bean sprout peel, bali duck, fermentation, commercial carcass pieces.